Anti-inflammatory activity of 4′, 6, 7-trihydroxy-5-methoxyflavone from Fridericia chica (Bonpl.) L.G.Lohmann. Issue 5 (3rd March 2020) - Lima, Joaquim C. S.; de Oliveira, Ruberlei Godinho; Silva, Virgínia C.; de Sousa Jr, Paulo Teixeira; Violante, Ivana M. P.; Macho, Antonio; Martins, Domingos Tabajara de Oliveira
Abstract: Fridericia chica, Bignoniaceae, is a tropical tree-creeper used as a traditional remedy for a number of diseases, highlighting inflammation. Our objective was to corroborate the popular anti-inflammatory use of the hydroethanolic extract from the leaves (HEFc) and of its isolated 4′, 6, 7-trihydroxy-5-methoxyflavone (5- O -methylscutellarein) [1 ], described here for the first time. Quantitative analysis indicated 8.77 ± 0.23 mg/g of this compound in the extract. Neither HEFc nor [1 ] was cytotoxic in vitro . In LPS-induced peritonitis in mice, oral pre-treatment with HEFc or [1 ] led to decreased leukocyte migration to the peritoneal cavity and a reduction in the concentrations of pro-inflammatory cytokines (TNFα and IL-1β). Also, the anti-inflammatory cytokine IL-10 was enhanced following treatment with [1 ]. Overall, these results validate the traditional use of Fridericia chica as anti-inflammatory, and indicate that the compound 5- O -methylscutellarein may participate in this effect. Abstract :